2022
DOI: 10.3390/foods11071007
|View full text |Cite
|
Sign up to set email alerts
|

A Multistep DNA-Based Methodology for Accurate Authentication of Sturgeon Species

Abstract: The sturgeons (order Acipenseriformes) are caviar producers and some of the most valuable fish species worldwide. Due to different reasons, wild populations are now at the brink of extinction. The high demand for caviar has led to the development of aquaculture for restocking and caviar production. Since the caviar from different species has different prices depending on the quality and attempts of commercial fraud based on species substitution have been found, correct species identification is more than neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The comparison and analysis of the data using the NCBI and BOLD databases showed that the similarity of each sample with the database was ≥98%, and the matching degree was high. The primers (set I) and self-designed COI gene primers (set II) achieved the same results of species identification, but neither could distinguish between A. baerii , A. gueldenstaedtii , A. naccari , A. persicus , and A. sinensis (Samples S1, S7, S11, S14, S19), which was consistent with the results of the previous reports [ 20 , 23 ]. In contrast, D-loop gene primer (set III) completely identified the sturgeon maternal information of all caviar samples, including A. baerii , A. gueldenstaedtii , A. schrenckii , H. dauricus, and H. huso ; with the majority of samples being identified as H. dauricus (52.4%) ( Table 2 ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The comparison and analysis of the data using the NCBI and BOLD databases showed that the similarity of each sample with the database was ≥98%, and the matching degree was high. The primers (set I) and self-designed COI gene primers (set II) achieved the same results of species identification, but neither could distinguish between A. baerii , A. gueldenstaedtii , A. naccari , A. persicus , and A. sinensis (Samples S1, S7, S11, S14, S19), which was consistent with the results of the previous reports [ 20 , 23 ]. In contrast, D-loop gene primer (set III) completely identified the sturgeon maternal information of all caviar samples, including A. baerii , A. gueldenstaedtii , A. schrenckii , H. dauricus, and H. huso ; with the majority of samples being identified as H. dauricus (52.4%) ( Table 2 ).…”
Section: Resultssupporting
confidence: 89%
“…This study used plant specific DNA barcodes ( tRNA-Leu ) [ 32 ] and fish universal primers ( COI ) [ 24 ] for identifying 21 batches of caviar, which ruled out the possibility of counterfeit caviar with non-sturgeon and plant-derived ingredients at the first step. Although COI -based DNA barcoding were suitable for detecting a wide range of animal species, several studies have shown limitations in the identification of sturgeon relatives [ 20 , 23 ] and we further confirmed this view. However, we successfully identified the maternal source of all caviar using primer set III based on the D-loop gene.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations